Unpacking social divisions of labor in markets: generalized blockmodeling and the network boom in stock photography - Glückler, Johannes; Panitz, Robert (Social networks, 2016)
During the advent of digital technology, the market for stock photography has undergone radical transformations that have disrupted incumbent businesses and produced new divisions of labor. Picture agencies have responded to this challenge with a veritable proliferation of inter-firm alliances. In the attempt to understand this network boom, this paper develops a theoretical link between the concept of regular equivalence and its capacity to detect intra-industry divisions of labor. Based on a network survey of picture agencies in Germany, a prespecified generalized blockmodel yields a valid representation of an increasing functional specialization of new value stages that translates into an extended social and spatial division of labor in ways that challenge a dualist theory of the division of creative labor.